Improving construction material and equipment logistics via simulation (2015)
(Eng) In this work, an analysis of the logistics processes of transport, distribution and storage of materials in foundation and structure activities of two reinforced concrete buildings located in the city of Bogotá D.C., in order to propose improvements in processes and increase productivity. The above is developed by performing discrete event simulation models. The work was carried out in three phases, in the first, the construction processes were characterized and a field work based on taking data, photos and videos; In the second stage, the simulation models were carried out for the real scenario, identified deficiencies and opportunities for improvement with which different theoretical scenarios were proposed, the which were compared in the third phase of the investigation. From the analysis of the results obtained, concluded that the simulation of discrete events allows observing the integration and behavior of the variables that intervene in the process, thus achieving, identifying shortcomings and proposing improvements with which the best scenario considering the cost-benefit ratio